Testing Maternal-Fetal Genotype Incompatibility with Mother-Offspring Pair Data - Wenjiang J. Fu; Ming Li; Kelian Sun; Yuehua Cui; Minping Qian; Roberto Romero (Journal of Proteomics and Genomics Research, 2013)
Maternal-fetal genotype (MFG) incompatibility has been shown to be strongly associated with a number of genetic diseases. Most current methods for the MFG test rely on parents-offspring trio genotype data and do not apply to mother-offspring pair data where paternal genotype is unavailable. In this paper, we developed a two-stage method for testing the allelic effect of given SNP through subgroup analysis of compatible MFG pairs and further tested the MFG incompatibility effect according to different scenarios determined by the allelic effect. Simulation studies demonstrated that this novel two-stage model is powerful in detecting the MFG incompatibility effect. This method can be implemented through publicly available statistical software, such as SAS, R, etc. We demonstrate with a case-control study of small for gestational age neonates that the method identified a SNP in the IGF2R gene with a significant allelic effect (p = 0.037), and a SNP in the IGF1 gene with a significant MFG incompatibility effect (OR = 0.75 and p = 0.033).
Keywords: Genotype-incompatibility